Preparation and Identification of Mixed Ligand Complexes Derived From New Azo Quinoline Ligand (Journal of the College of Basic Education, 2022)
This search included preparing of new mixed ligand complexes of Cobalt (II) and Nickel (II) and Copper (II) and Zinc (II) with new heterocyclic azo – quinoline ligand (HL1) (P-TAQ) and ligand (HL2)(2-Aminophenol), with the mole ratio metal: (HL1): (HL2) (1: 1: 1). The azo – quinoline ligand has been prepared in two steps, the first included preparation of the Schiff base (SB) (N-(1-(4-aminophenyl)ethylidene)-4-methylaniline ) from condensation reaction of P-Toluidine with ( P-Aminoacetophenone ), while the second involved coupling of Schiff base's diazonium salt with (8-Hydroxyquinoline). The geometrical figures of prepared complexes, suggested depending upon the results of electronic spectra data, Infrared Spectra, magnetic susceptibility and molar conductivity